Long term farming systems affect soils potential for N2O production and reduction processes under denitrifying conditions. (November 2017) - Krause, Hans-Martin; Thonar, Cécile; Eschenbach, Wolfram; Well, Reinhard; Mäder, Paul; Behrens, Sebastian; Kappler, Andreas; Gattinger, Andreas
Abstract: N2 O is a potent greenhouse gas with an atmospheric lifetime of 114 years which also contributes to ozone layer destruction. Mitigating N2 O emissions is especially challenging to the agricultural sector that is responsible for the majority of anthropogenic N2 O release. In order to develop effective mitigation strategies, a detailed understanding of drivers for N2 O production and reduction in agriculturally managed soils is needed. Denitrification is recognized as one of the most important source processes for N2 O emissions from soils. However, the last step in denitrification, the reduction of N2 O to N2 is the only known sink for N2 O in soil. Although the impact of single parameters on denitrification is quite well documented, there is still a knowledge gap when it comes to the impact of complex farming systems on N2 O production and reduction. In this experiment, we incubated soil samples from the DOK long term field trial in Therwil/Switzerland comparing organic (BIOORG) and conventional (CONMIN) farming systems with an a non-fertilized control (NOFERT). Soil samples were incubated under 90% WFPS after fertilization with NH4 15 NO3 equivalent to a moderate fertilization event in the field with 40 kg N ha −1 . In order to assess soil's potential for N2 O production and reduction, we combined direct measurements of denitrification end products N2 O and N2 with molecular analysis of functional denitrifying communities involved in NO2 − and N2 O reduction on DNA and mRNA levels. In order to monitor N cycling processes under the chosen conditions, stable isotope tracing was employed to quantify nitrification and NO3 − consumption rates. Results revealed increased NO3 − consumption and greatest potential for N2 O emissions in BIOORG as a result of increased soil organic carbon contents. Production of N2 was similar in BIOORG and CONMIN and significantly lower in NOFERT, most likely due to significantly decreased pH inhibiting N2 O reduction. This caused the greatest N2 O/(N2 O + N2 ) ratios in NOFERT (0.88 ± 0.02) followed by BIOORG (0.79 ± 0.01) and CONMIN (0.68 ± 0.02) (p < 0.001). Lowest N2 O/(N2 O + N2 ) ratios in CONMIN were reflected by lowest N2 O emissions and coincided with elevated nosZ transcript copies in the beginning of incubation. Although highest N2 O emissions in BIOORG were detected, the incubation setup cannot directly be translated to field conditions. Nevertheless, our results emphasize that farming system induced changes on soil geochemical parameters like soil pH and soil organic carbon affect microbial N2 O production and reduction processes during denitrification. Highlights: Higher N2 O/(N2 O + N2 ) molar ratio in organic compared to conventional farming system. Low N2 O reduction in unfertilized farming system due to low pH. Highest nosZ transcripts in conventional farming systems coincide with N2 O emissions.